Screening of gestational diabetes mellitus using one-step versus two-step method: a comparative study - Khenwar, Deepti; Agarwal, Juhi; Shriastava, Sushruta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Gestational diabetes mellitus (GDM) is defined as carbohydrate intolerance of variable severity with onset or first recognition during the present pregnancy. It affects 7% of all pregnancies worldwide and in India it ranges from 6 to 9% in rural and 12 to 21% in urban area. The aim of this study was to compare the DIPSI criteria with the two-step method (Carpenter and Couston criteria.) and to study merits and demerits of one step and two step tests for GDM. Methods: A total 400 pregnant women of gestational age between 24-28 weeks attending antenatal clinic at this study tertiary care center were enrolled in this study. 200 pregnant women were enrolled in each of the study group (Group I OGTT and Group II DIPSI). Results: In Group I (OGTT) screening 47 (23.5%) were tested positive. In Group II cases, screening test results were found positive among 44 (22%). Out of 95 high-risk pregnant women 38 (40%) were positive for GDM by OGTT and 34 (35.78%) were positive by DIPSI. Out of 305 non high-risk pregnant women, 9 (2.95%) were positive for GDM by OGTT and 10 (3.27%) were positive by DIPSI. Conclusions: Present study concludes that DIPSI is the test which can predict GDM in population comparable to another test like OGTT. Also, India’s major population reside in rural areas, ANC are mostly conducted by ANM, therefore screening test should be easy to perform and interpret.